Odpowiedzi

2009-05-18T17:38:42+02:00
A) x/3-5/6=1/12-x/2 *12
4x - 10 = 1 - 6x
4x + 6x = 1+10
10x = 11/10
x = 11/10
b) x/2-3/4=7/8+x/4 * 8
4x -6 =7 + 2x
4x - 2x = 7 + 6
2x = 13/2
x = 6,5
c) 7/9+x/2=3/2-x/18 * 18
14 + 9X = 27 - x
9x + x = 27 - 14
10x = 13/10
x = 1,3
d) x/9+1/2=5/4-x/6+1/12 * 108
12x+54=135 -18x+9
12x+18x = 90
30x=90/30
x=3


14 4 14
2009-05-18T17:42:06+02:00
A. x/3-5/6=1/12-x/2 *12
4x - 10 = 1 - 6x
4x + 6x = 1+10
10x = 11/10


x = 11/10



B. x/2-3/4=7/8+x/4 * 8
4x -6 =7 + 2x
4x - 2x = 7 + 6
2x = 13/2



x = 6,5



C./9+x/2=3/2-x/18 * 18
14 + 9X = 27 - x
9x + x = 27 - 14
10x = 13/10




x = 1,3
D./9+1/2=5/4-x/6+1/12 * 108
12x+54=135 -18x+9
12x+18x = 90
30x=90/30




x=3
4 3 4